Familial temperature-sensitive auditory neuropathy/auditory dyssynchrony - (:unkn) unknown (MEDITERRANEAN SOC OTOLOGY & AUDIOLOGY, 2007)
Auditory neuropathy/auditory dyssynchrony is a hearing disorder characterized by impairment of neural synchrony in the presence of a normal cochlear outer hair cell function. Clinical findings are normal hearing or sensorineural hearing loss, absent/abnormal auditory brainstem response, normal otoacoustic emissions, normal cochlear microphonics, and poor speech perception abilities that are disproportionate to the hearing sensitivity. We identified 5 patients, all related, with auditory neuropathy. Pure-tone audiometry, acoustic immittancemetry, evoked potentials, otoacoustic emission tests, and magnetic resonance imaging were per-formed on all of them. We followed the patients for 5 years. We determined that their audiologic findings showed variations when they had influenza, due to high body temperature.
Keywords: SENSORY NEUROPATHY; HEREDITARY MOTOR; POTENTIALS; DEAFNESS